СТОМАТОЛОГИЯ ТЕРМИНЛАРНИНГ ЭТИМОЛОГИК ВА МОРФОЛОГИК ХУСУСИЯТЛАРИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article is devoted to the etymological and morphological characteristics of dental terms. Based on the results of analyzed examples related to the field of dentistry, it has been proven that terms denoting disease, pathologies, symptoms, infectious diseases and dental medical equipment mainly belong to the Greek-Latin vocabulary.
Keywords: dental terms, affixation, morphology, borrowed morphemes, word formation.